Understanding Hridroga in the Light of Santarpana and Lifestyle Disorders (AYUSHDHARA, 2025)
Hridroga is one among the serious life-threatening condition which affects Hridaya is due to the deranged Tridosha and the vitiation of Rasadhaatu. Hridroga is enlisted under Apatarpanottha Vikaras. When we look into the Nidanas of Hridroga, most of them point towards features of Apatarpana meaning undernourishment or depletion. Metabolic syndrome is an asymptomatic pathophysiological condition characterized by central obesity, high blood pressure, insulin resistance, dyslipidemia and hyperglycemia. In the present era, the pattern of cardiovascular disorders has shifted, with increasing prevalence linked to sedentary lifestyle, over-nutrition, obesity metabolic syndrome that are characteristic of Santarpana. This study is an attempt to reinterpret and derive Santarpanottha Nidānas that may lead to Hṛidroga, aligning classical concepts with modern clinical presentations.